Use of a screening tool and primary health care gerontology nurse specialist for high-needs older people. Issue 1 (2nd January 2017) - King, Anna; Boyd, Michal; Dagley, Lynelle
Abstract : Objectives : To describe implementation of an innovative gerontology nurse specialist role within one primary health organisation in Auckland, New Zealand. Quantitative outcomes of the screening tool as well as the nurse specialist assessment will be presented. Method : The intervention involved use of the Brief Risk Identification for Geriatric Health Tool (BRIGHT) to identify high-needs older people with subsequent comprehensive geriatric assessment (CGA) performed by the gerontology nurse specialist. Results : A total 384 of the 416 BRIGHTs were completed (92% response rate) and 15% of these were identified as high risk ( n = 57). The BRIGHTs for high-risk older people revealed the highest scoring question was 'needing help with housework' (26%). The most frequent intervention by the gerontology nurse specialist was education (30%). Conclusions : The primary health care gerontology nurse specialist model delivers a proactive case finding and specialist gerontology intervention for older people at high risk of functional or health decline.